Neuraminic acid is alpha 2-->3 linked in the lipooligosaccharide of Neisseria meningitidis serogroup B strain 6275. - Yamasaki, R (1993)
We have analyzed the sialylated lipooligosaccharide of Neisseria meningitidis 6275. Sialylated oligosaccharide released from strain 6275 lipooligosaccharide by mild hydrolysis was determined to contain N-acetylneuraminic acid linked alpha 2-->3 to terminal galactose as shown below. [formula: see text]